Prise En Charge Des Péritonites Aiguës Dans Un Hôpital De District En Afrique Sub-saharienne : Cas Du Bénin - Bio Tamou Sambo; Salako Alexandre Allodé; Didier Sewadé Wekpon; Djifid Morel Séto; Montcho Adrien Hodonou; Babatoundé Dossou (European Scientific Journal, ESJ, 2017)
Introduction: Peritonitis remains a public health problem in Africa. We aim to describe the epidemiological, etiological and therapeutic aspects of acute peritonitis in a district hospital in Sub Saharan Africa. Methods: This was a descriptive study with prospective data collection over a period of 15 months from May 1 st 2015 to July 31st 2016 in Bembereke district hospital. It has taken into account all the patients managed in the general surgery department for acute generalized peritonitis that has been confirmed at laparotomy. Results: Fifty-three patients, 38 men (71.7 %) and 15 women (28.3 %) had been registered. The average age of the patients was 19.8 ± 16.9 years. The main etiologies were: non-traumatic ileal perforation from typhoid infection 52.8%; perforated gastric or duodenal ulcer 17%; complicated appendicitis and abdominal traumas 11.3% each one. Twenty nine patients (54.7%) have been operated by a surgeon and the 24 remaining (45.3%) by a general practitioner with surgical skills. Twenty one patients (39.6%) had postoperative complications of which 11 cases of parietal suppurations (52.4%). The mortality rate was 11.3%. The mean hospital stay was 22.5 ± 4 days. Conclusion: In northern-Benin, peritonitis remains dominated by the complications of typhoid fever. The mortality rate remains high. Prevention requires good hygiene and awareness of early consultations.